Percepções, sensações e sentimentos da morte: leitura e atualização do olhar sobre a criança em Lobato, Duprè e Viana - Borges, Matheus Taylor Souza (2024)
It is not uncommon for child characters to be found in Brazilian literature books, whether they are children oriented or not. However, the choices made in the different contexts of creating these characters carry great complexity, involving a range of factors which deserve reflection. Thus, the present study aims at analyzing how some authors from the 20th century - an important moment of transformation for Brazilian society, including what concerns the legislation responsible for protecting children and childhood - were capable of different representations of child characters in their aesthetic projects, associated with experiences that refer to death, such as war and trauma. From the theoretical-critical perspective of Wolfgang Iser (2011), in which he establishes the notion between game and representation, a critical/reflexive reading will be carried out, aiming to update the view on the child represented in the literary corpora selected in the books A chave do tamanho (2021), by Monteiro Lobato, Éramos Seis (2012), by Maria José Duprè and in the short stories Olhos de Fogo (1981) and A Mulher das Mangabas (1974), both written by Antonio Carlos Viana. Bearing in mind that these literary works depict child characters, the research also aims to observe the representative choices made by the authors, given their own production contexts, assessing variants, such as historical moment, target audience and the themes each author relates to the figure of the child in the texts mentioned. Throughout the research, the compositional resources that these narratives use to avoid the instruments of control of the imaginary are also investigated, according to Luiz Costa Lima's terminology, in A Trilogia do Controle (2007), by associating the child figure with themes such as loss, death and self-discovery, in processes of subjectivation, as we will reflect on Michel Foucault's theories about the subject's control mechanisms in Microfísica do Poder (2001). We will also use Ariès' theory (1981) to understand the historical construction of the child9s figure, making counterpoints with some moments of Brazilian legislation throughout the 20th century, seeking to clarify the relationships between the representation of the child element, imaginary, and power in the segments selected.